Edukasi Potensi Pelajar Melalui Program Kelas Kreatif Pembuatan Kerajinan Tangan di Desa Lubuk Banjar - Debbi, Ristianni Mayka; Ningsih, Putri; Sari, Putri Ayu Cinta; Mardalena, Ervin; Dahlia, Dahlia (Indo-MathEdu Intellectuals Journal, 2026)
Lubuk Banjar Village has a variety of local potentials that have not been optimally utilized as learning resources for students. This study aims to describe the implementation and impact of the Creative Handicraft Class Program as a means of developing students' skills, creativity, and character based on local potential. This program is implemented through a structured learning approach by linking handicraft practice materials with the village's local resources and culture. Data was collected through observation of activities, documentation of work results, and participant reflections during the learning process. The results of the program implementation showed an increase in learning interest, innovation skills, and the growth of students' confidence and pride in their own work and the cultural identity of Lubuk Banjar Village. These findings indicate that the utilization of local potential through creative classes can be an effective contextual learning strategy in supporting individual development and strengthening the village community.